Assessing the Inbound Tourism Efficiency of European Countries in China: 2006-2019 - Liudan Wu; Lili Hao; Lingzhi Wu; Ruize Gao; Ji Chen (Amfiteatru Economic, 2023)
Assessing inbound tourism efficiency helps to understand the potential levels and constraints of inbound tourism flows. In this study, 35 European countries and China were selected as samples and influencing factors of tourism efficiency were constructed within the gravity model (GM) and stochastic frontier analysis (SFA). Taking into account individual heterogeneity, a true fixed-effects stochastic frontier gravity model (TFE-SFA-GM) was developed and empirically analysed using data from 2006 to 2019. The results show that (1) the inbound tourism efficiency of European countries in China is jointly affected by many core factors, such as economic scale, geographic distance, and population size on both sides; (2) the inefficiency factors that affect the inbound tourism efficiency of European countries in China are diversified;(3) the inbound tourism efficiency of European countries in China generally shows an upward trend during the sample period, but there are significant differences in the gap between the frontier level of inbound tourism flow in China and the actual inbound tourism flow. These findings imply that to better attract European tourists, China must continue to maintain and strengthen economic and trade relations with European countries, create a favourable security environment for tourism, highlight the integration of international tourism resources with Chinese culture, and continue to promote them in Europe.
Keywords: A10; C23; L83; Z31; 330; stochastic frontier analysis; gravity model; true fixed effects stochastic frontier analysis gravity model; inbound tourism efficiency.